Fičko po Jugoslaviji Zvezda domačega avtomobilizma med cestami in spomini - Pogačar, Martin (Kulturni spomin, 2016)
The monograph addresses the question of Yugoslav automobile heritage and memory. The vehicle of choice in this endeavour is the Crvena Zastava make Zastava 750, better known as Fičko. The author traces the post-Yugoslav stories of the car as an object that left a deep mark in automobile and memorial landscapes of the latter 20th and early 21st centuries. As an object of memory and tinkering, Fičko is used as a metaphorical vehicle to address the issues related to nostalgia and memory, but also to engage with complex questions concerning automobile heritage and nationalisation of memory and industrial. Through the analysis of various practices of re-presencing the past he author thematises the relationship between affect and automobility in (digital) popular culture and not least the relationship to the Yugoslav socialist past in general.